When Does Transparency Backfire? Putting Jeremy Bentham's Theory of General Prevention to the Experimental Test. Issue 4 (4th October 2019) - Engel, Christoph
Abstract : Jeremy Bentham brought enlightenment to criminal policy. He argued that the primary purpose of criminal sanctions should be deterring future crime. To that end he advocated complete transparency. This article investigates Bentham's intuition in a public goods lab experiment by manipulating how much information on punishment experienced by others is available to would‐be offenders. Compared with the tone that Jeremy Bentham set, the result is unexpected: when would‐be offenders learn about punishment of others at the individual level, they contribute much less to the public project. This is due to an inevitable side effect. Information about punishment is only meaningful together with information about the infraction.